An Exploratory Analysis of Content Structure and Cognitive Structure in the Context of a Mathematics Instructional Unit - Geeslin, William Edward ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
Digraphs, graphs and task analysis were used to map out the content structure of a programed text (SMSG) in elementary probability; mathematical structure was operationally defined as the relationship between concepts within a set of abstract systems. The word association technique (WA) and paragraph construction technique (PC) were used to measure the existing relations (cognitive structure) in S's memory with respect to the probability theory present in the text. The purpose of this study was to measure the influence of content structure (mathematical structure) of the text on the subjects' cognitive structure. Control and experimental Ss (W=181) were sixth-grade, eighth-grade and high-school (grades 9-12) students. Experimental Ss read the probability text while the others read a programed text unrelated to probability. Ss were pre- and posttested and given retention tests. Results indicated that the experimental Ss' measured cognitive structure highly resembled the text's content structure following instruction. The WA and PC test also appeared to be useful for formative evaluation of the programed text and gave different information than did achievement tests. (JP)
ERIC Note: Ph.D. Dissertation, Stanford University.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cognitive Development; Cognitive Processes; Doctoral Dissertations; Elementary School Mathematics; Learning; Learning Processes; Mathematics Education; Probability; Programed Instruction; Research; Secondary School Mathematics; Structural Analysis; School Mathematics Study Group